Membangun Kesadaran Masyarakat akan Pentingnya Tabungan Haji dalam Perencanaan Keuangan Ibadah Haji - Anita, Amalia Wahyu; Aminah, Siti; Selviasari, Rike (Welfare : Jurnal Pengabdian Masyarakat, 2024)
Financial planning for the pilgrimage (hajj) should be conducted early to ensure a more organized and systematic approach, one of which is through hajj savings. Hajj savings is a service offered by Bank Syariah Indonesia (BSI) to help customers save gradually for the expenses of their hajj journey. This community service activity aims to provide financial literacy to the public, particularly BSI customers, regarding the importance of financial planning for hajj. The method used in this service is to integrate academic learning with community service, known as Service Learning, which provides students the opportunity to apply the theories learned in class to practical and beneficial real-life situations. The results of this service show an increase in understanding related to the importance of planning for the pilgrimage through hajj savings. Some participants then opened a Hajj Savings account with the Wadi'ah Yad Dhammama contract.